Pan-cancer analysis reveals NAA50 as a cancer prognosis and immune infiltration-related biomarker - Fang, Tao; Wang, Dingxin; Li, Rongyang; Yu, Wenhao; Tian, Hui (Frontiers in Genetics, 2022)
Background: N-Alpha-Acetyltransferase 50 (NAA50) has acetyltransferase activity and is essential for proper chromosome segregation. However, the function and mechanism of NAA50 expression in cancer development was still unclear. Here, we systematically researched the function and mechanism of NAA50 in pan-cancer, and further verified the results of NAA50 in lung adenocarcinoma (LUAD). Methods: In this study, using the online databases TIMER2.0, SangerBox3.0, HPA, UCSC, GEPIA, cBioPortal, UALCAN, TISIDB, CancerSEA and LinkedOmics, we focused on the relevance between NAA50 and oncogenesis, progression, methylation, immune infiltration, function and prognosis. In addition, the proliferation of cells was detected by CCK-8 and Edu assay. Finally, we analyzed the relationship between the expression of NAA50 and cell cycle related proteins Results: Pan-cancer analysis indicated that NAA50 was overexpressed in most cancers. And there was a significant correlation between NAA50 expression and the prognosis of cancer patients. In the meantime, NAA50 gene changes occur in a variety of tumors. Compared with normal tissues, the methylation level of NAA50 promoter increased in most cancer tissues. In addition, the results exhibited that in most cancers, NAA50 was significantly positively correlated with bone myeloid-derived suppressor cell (MDSC) infiltration and negatively correlated with T cell NK infiltration. Moreover, functional enrichment indicated that NAA50 regulates cell cycle and proliferation in LUAD. In vitro experiments testified that knockout of NAA50 could significantly inhibit the proliferation of LUAD. Conclusions: NAA50 may be a potential biomarker and oncogene of pan-cancer, especially LUAD, which may promote the occurrence and development of tumors through different mechanisms. Furthermore, NAA50 was bound up with to immune cell infiltration in pan-cancer, meaning NAA50 may be an important therapeutic target for human cancers.